2001
DOI: 10.1095/biolreprod64.5.1575
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Chicken Vasoactive Intestinal Polypeptide Receptor Complementary DNA, Tissue Distribution and Chromosomal Localization1

Abstract: Chicken vasoactive intestinal polypeptide receptor (VIPR) cDNA was cloned by the reverse transcription-polymerase chain reaction method using primers designed on the basis of other species of VIPR cDNA. The cDNA obtained was sequenced by the dideoxy-mediated chain-termination method. Of the 2227 nucleotides that were sequenced, 84, 855, and 1338 bases represent the 5'-untranslated region (UTR), the 3'-UTR, and the open reading frame that predicts a peptide of 446 amino acids. The cDNA of the chicken VIPR shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Accession numbers of the sequences are: mouse, P97751; rat, P97751; human, P32241; pig, Q28992; frog, Q9YHC6 and goldfish, Q90308. The chicken sequence is taken from Kansaku et al 2001. revealed the presence of seven conserved transmembrane domains (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accession numbers of the sequences are: mouse, P97751; rat, P97751; human, P32241; pig, Q28992; frog, Q9YHC6 and goldfish, Q90308. The chicken sequence is taken from Kansaku et al 2001. revealed the presence of seven conserved transmembrane domains (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Names and abbreviations and accession numbers for all the sequences shown: rat VPAC 1 , P97751; rat VPAC 2 , P35000; rat PAC 1 , P32215; rat sec, P23811; human V PAC 1 , P32241; human VPAC 2 , P41587; human PAC 1 , P41586; human sec, P47872; human GHRH, P43220 (used as the outgroup); mouse VPAC 1 , P97751; mouse VPAC 2 , P41587; mouse PAC 1 , P70205; frog VPAC 1 , Q9YHC6; pig VPAC 1 , Q28992; goldfish VPAC 1 , Q90308; goldfish PAC 1 , O73769; cattle PAC 1 , Q29627; toad PAC 1 , Q9PTK1; Fugu VPAC 1 A, AJ296144; Fugu VPAC 1 B, AJ296143; Fugu VPAC 2 A, AJ408877; Fugu VPAC 2 B, AJ408878; Fugu PAC 1 A, AJ490804; Fugu PAC 1 B, AJ494861; rabbit sec, O46502. The chicken sequences for VPAC 1 and PAC 1 were taken from Kansaku et al 2001 andPeeters et al 1999 respectively. Sec, secretin receptor. receptors in humans and rats.…”
Section: Discussionmentioning
confidence: 99%
“…A single VIP receptor has been cloned in turkeys and chickens that exhibits 55-65% sequence identity with VIP1 and VIP2 receptors in mammals (Kansaku et al, 2001;You et al, 2001). Using the same 125 I-VIP employed here (human/porcine/rat; Perkin-Elmer Life Sciences, 2 Sociality information for the 139 estrildids has been compiled into a table, available from J.L.G.…”
Section: Avian Neuropeptide Receptors and Selection Of Iodinated Ligandsmentioning
confidence: 99%
“…A single VIP receptor has been cloned in turkeys and chickens that exhibits 55-65% sequence identity with VIP1 and VIP2 receptors in mammals (Kansaku et al, 2001;You et al, 2001). Using the same 125 I-VIP employed here (human/porcine/rat; Perkin-Elmer Life Sciences, Boston MA), it has been shown that specific binding sites in turkey telencephalon exhibit a high affinity for both VIP and pituitary adenylate cyclase-activating polypeptide (PACAP) (Zawilska et al, 2004).…”
Section: Avian Neuropeptide Receptors and Selection Of Iodinated Ligandsmentioning
confidence: 99%
“…As a receptor of VIP, VIPR is activated by VIP to give rise to secretion and release of PRL (el Halawani et al, 1990). The VIPR gene has proved to be involved in the regulation of broodiness in avian, as evidenced by the endocrine mechanism of broodiness and expression in vivo and in vitro (Rozenboim and el Halawani, 1993;Kansaku et al, 2001;Chaiseha et al, 2004). The VIPR-1 gene was expressed in the hypothalamus and pituitary, primarily in the latter, and only the differential mRNA expression of the VIPR-1 gene in the pituitary was associated with reproductive changes (You et al, 2001), suggesting that the VIPR-1 gene is an important candidate gene for egg-laying quails.…”
Section: Introductionmentioning
confidence: 99%